Erratum Non-penetrating Eye Injuries in Victims of Bomb Blasts and Mine Blasts - Mustafa Iqbal, Mumtaz Alam (Pakistan Journal of Ophthalmology, 2018)
In PJO Vol. 29; Issue 1; 2013, on page 10, Table 4 Final Visual Acuity was missing.